Congenital tracheoesophageal fistula without atresia: an incidental finding - Oğuzkurt, Levent; Balkancı, Ferhun; Arıyürek, Macit (The Turkish Journal of Pediatrics, 1997)
A four-year-old boy who had a long history of upper respiratory tract infections and growth retardation was admitted because of recurrent abdominal pain. During upper gastrointestinal series to search for a gastric or duodenal ulcer, the examiner noticed a minute amount of contrast medium within the trachea. Repeat esophagography on an angiographic table led to the correct diagnosis of a congenital H-type fistula. The patient did not have the classical symptoms of a history of choking and cyanosis after feeding during infancy or recurrent lower respiratory tract infections. The only finding consistent with a fistula was growth retardation, and the diagnosis was established incidentally during a work-up for abdominal pain.
Keywords: tracheoesophageal fistula; without atresia